Optical properties of Alexa™ 488 and Cy™5 immobilized on a glass surface. (January 2005) - Wang, Lili; Gaigalas, Adolfas K.; Reipa, Vytas
The absorption and emission spectra were measured for Cy™5 and Alexa™ 488 fluorophores confined on a glass surface. The data were obtained using fluorometry and spectroscopic ellipsometry. Red shifts of the surface-immobilized fluorophore absorption spectra relative to the fluorophore spectra in aqueous solution were observed using both methods. We interpret these red shifts in terms of a change in the polarizability and polarity of the effective solvent. A formula is given that can be used to estimate expected shifts in absorption and emission maxima for surface-immobilized fluorophores. Spectroscopic ellipsometry measurements provide identification of the fluorophores confined on a glass surface. These results suggest that the design of microarray detection systems should be based on the optical properties of fluorophores attached to the surface and not on the optical properties of fluorophores in solution.